(untitled) (Gestionar: revista de empresa y gobierno, 2022)
The objective of this research was to identify the perceptions of rice micro-producers regarding the associative strategy, to improve the competitiveness of their production in the district of Lambayeque, Peru. The study was correlational, non-experimental, with a quantitative cross-sectional approach. The study population consisted of 80 micro-producers of rice cultivation, a Likert scale survey was applied, one per study variable, which were subjected to expert judgment and a reliability test proven with Cronbach’s Alpha (0.88). The results show that the producers perceive as positive and are accessible to associate to enhance their productive activity and achieve better competitiveness in their market.